2010
DOI: 10.3171/2010.3.jns091882
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality following treatment of intracranial hemangiopericytoma

Abstract: Treatment with gross-total resection provides the greatest survival advantage and should be pursued aggressively as an initial therapy. The addition of postoperative adjuvant radiation does not seem to confer a survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
5
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 86 publications
9
118
5
12
Order By: Relevance
“…The effective radiation dose is quoted by most studies to be [50 Gy [17][18][19][21][22][23][24]. In a recent systematic review of 563 intracranial HPCs cases (277 had follow-up data), Rutkowski et al [25] reported that patients receiving [50 Gy of radiation had worse survival outcomes (median Table 2 Cases of hemangiopericytoma of the spine described in present and previous reports survival 4 vs. 18.6 years, p \ 0.01). This study notes the possibility of selection biases in tumor quality and more aggressive tumors receiving higher doses.…”
Section: Adjuvant Treatmentmentioning
confidence: 98%
“…The effective radiation dose is quoted by most studies to be [50 Gy [17][18][19][21][22][23][24]. In a recent systematic review of 563 intracranial HPCs cases (277 had follow-up data), Rutkowski et al [25] reported that patients receiving [50 Gy of radiation had worse survival outcomes (median Table 2 Cases of hemangiopericytoma of the spine described in present and previous reports survival 4 vs. 18.6 years, p \ 0.01). This study notes the possibility of selection biases in tumor quality and more aggressive tumors receiving higher doses.…”
Section: Adjuvant Treatmentmentioning
confidence: 98%
“…4 Histologically, hemangiopericytoma arises from pericytes of Zimmerman or pericapillary cells and can occur anywhere where capillaries are found. 2,8,9 It has been classified as a mesenchymal tumor of the meninges and further subclassified into 2 histologic types, hemangiopericytoma and anaplastic hemangiopericytoma (corresponding to WHO grades II or III) by the WHO in 2007. 10 The literature on CT and MR imaging of intracranial meningeal hemangiopericytomas is currently limited.…”
mentioning
confidence: 99%
“…The median survival from the time of diagnosis is approximately 13 years. 24 Dural metastasis can also look like meningiomas, with a similar enhancing pattern and dural tail. It is estimated that dural metastases are found in 8%-9% of patients with advanced systemic cancer at autopsy.…”
Section: Lesions Mimicking Meningiomasmentioning
confidence: 99%
“…Hemangiopericytoma is a rare intracranial malignancy believed to represent 2%-3% of all primary meningeal tumors. 24 Hemangiopericytomas were initially considered a subgroup of meningioma (angioblastic variant), 1 but since 1993 the WHO has classified them as a distinct entity. 27 Hemangiopericytomas are known for their aggressive behavior, high recurrence rate, and potential for metastasis.…”
Section: Lesions Mimicking Meningiomasmentioning
confidence: 99%